Managing trade but mangling the consumer: Reflections on the EEC's and West Germany's experience with the MFA - Dean Spinanger; Joachim Zietz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
The paper begins with a brief overview of the developments leading up to the MFA and the role played by the European Economic Community (EEC), the largest market in the world for textiles and clothing. Next, the EEC is used as a reference point for an overview of protectionistic measures taken within the framework of or sanctioned by the MFA. Finally, it is examined how these measures affected an important individual MFA product at a low level of aggregation. This analysis is performed for shirts imported to West Germany.
Keywords: 330